Foot-amulets: a possible amuletic value - Mordà, Barbara (Buried History: The Journal of the Australian Institute of Archaeology, 2012)
A number of foot-shaped objects have been found in Bronze Age graves in the region of Messará, Crete. Previous scholars have suggested they may be amulets or talismans. One hypothesis advanced in the late 1960s proposed that they gave protection from poisonous snakes bites and were connected to the Minoan Snake Goddess cult. This paper reports on a new interpretative hypothesis for these objects based on an analysis of ancient sources, and paleontological and herpetological research. It also draws attention to analogous findings from Egyptian contexts, contemporary to those of Minoan Crete, to search for possible origins and typological relationships for the so called foot-amulets.